In memory of prof. Mario Raffa - Pencarelli, Tonino; Cesaroni, Francesca Maria; Demartini, Paola (Piccola Impresa / Small Business, 2022)
In this note, the Editor-in-chief and the Editorial Team of Piccola Impresa/Small Business would like to remind the memory of Professor Mario Raffa, who recently passed away. Mario Raffa served as co-editor of our journal for several years and made a significant contribution to the consolidation of its editorial project and the development of research on entrepreneurship and SMEs. He was a prestigious scholar, a lively mind, a fundamental point of reference for colleagues and students, and a great innovator, capable of looking ahead, devising ever new projects and involving others in facing ever new challenges. We thank him for his generous contribution to the Journal and for the dedication with which he animated the community of entrepreneurship and small business scholars.